Implementasi Sistem Monitoring Tenaga Kerja Bongkar Muat (SIMON TKBM) terhadap Kegiatan Bongkar Muat di Pelabuhan Tanjung Perak - Dhea Putri Ananda Br Sitepu; Otri Wani Sihaloho; Dyah Ratnaningsih; Intan Sianturi (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the use of SIMON TKBM, identify obstacles in its implementation, and evaluate its impact on the efficiency of loading and unloading activities at Tanjung Perak Port. A quantitative approach was used involving a population consisting of 1480 loading and unloading workers (TKBM) at the port. The research sample was calculated using the Slovin formula with a margin of error of 10%, resulting in a total of 90 representative respondents. Data was collected through a questionnaire with 17 statements and then analyzed using validity, reliability and multiple linear regression tests to identify the relationship between the use of SIMON TKBM, implementation obstacles and its impact on loading and unloading efficiency. Referring to the validity and reliability test results, it shows that all questionnaire items are valid and reliable (Cronbach's Alpha = 0.893). Multiple linear regression analysis shows that the System (X1) and User (X2) variables have a positive effect on Interaction (Y), with the largest contribution coming from the user factor (coefficient = 0.301; significance = 0.003). Meanwhile, the System variable has a low and insignificant influence (coefficient = 0.090; significance = 0.395), which indicates the existence of technical problems in the system. The multiple correlation coefficient value of 0.519 indicates a moderate relationship between the three variables. These findings conclude that the implementation of SIMON TKBM is quite effective in supporting loading and unloading activities, especially with active user support, although technical improvements and identification of other external factors that influence system effectiveness are still needed.